Organic nanoparticles from different fuel blends: in vitro toxicity and inflammatory potential. Issue 11 (22nd September 2014) - Gualtieri, Maurizio; Capasso, Laura; D'Anna, Andrea; Camatini, Marina
ABSTRACT Despite the well‐established link between particulate vehicle emissions and adverse health effects, the biological effects produced by ultrafine particles generated from fuel combustion need to be investigated. The biological impact of nano‐sized organic carbon particles in the size range 3–7 nm, obtained from an engine fuelled with a standard diesel and four diesel fuels doped with additives of commercial interest is reported. Our data showed that the number of particles < 10 nm is to a very small extent reduced by diesel particle filters, despite its ability to trap micrometric and submicrometric particulates, and that there is a correlation between the additives used and the chemical characteristics of the nanoparticles sampled. The results show that the different nano‐sized organic carbon particles induce cytotoxic and proinflammatory effects on the in vitro systems A549 (epithelial cells) and BEAS‐2B (bronchial cells). All the fuels tested are able to induce the release of proinflammatory interleukins 8 and 6; moreover, the IC50 values show that the additives can increase the toxic potential of particles 10 times. Further analyses are therefore needed to better define the potential impact of organic ultrafine particles on human health. Copyright © 2014 John Wiley & Sons, Ltd.